Niemann-Pick Disease: An Approach for Diagnosis in Adulthood (2019)
Niemann-Pick (NP) disease is a rare, autosomal recessive disorder characterized by visceromegaly and neurological alterations due to the excessive storage of lipids, sphingomyelin, and cholesterol. It commonly affects the child population, and only 6% of it occurs in the adult population. Type A is classified as the acute form, type B is the latest and with the best prognosis, and type C is characterized by neurological alteration. The diagnosis is based on enzymatic tests and genetic sequencing, with the latter being the diagnostic confirmation test. No specific treatment exists for this entity, although some patients with NPC type C may benefit from pharmacological treatment with miglustat. The objective of this paper is to describe the clinical characteristics of a grown patient with Niemann-Pick diagnosis type B. This article reports the case of a 55-year-old adult patient with a three-year clinical history consisting of splenomegaly and hematological disorders, without neurological symptoms ruling out frequent pathologies. Type B NP disease is diagnosed by a mutation in the sphingomyelin phosphodiesterase 1 (SMPD1) gene. The patient was receiving multidisciplinary support treatment. Although NP disease is a rare disease according to the literature, it is important to consider this group of disorders as a differential diagnosis, when other more common pathologies have been ruled out in patients with isolated splenomegaly and thrombocytopenia